Evaluation of dental health and thickness of mandibular inferior cortex among menopaused Iraqi cigarette smokers sample by the aid of using digital panoramic radiography (Mustansiria Dental Journal, 2018)
Smoking is linked to osteoporosis through its anti-estrogenic effect in womenwhich results in premature menopause in smokers and increased bone resorption iscorrelated with estrogen loss in menopause women. The aim of this study is toevaluate the effects of smoking and hormonal changes on the thickness of mandibularinferior cortex and the dentition status in both maxilla and mandible (DMFT) inmenopausal females and to estimate the value of panoramic radiographic findings inassessing the possibility of latent osteoporosis. Panoramic images for 80 healthy,median stature, smokers and non-smokers Iraqi female subjects aged (20-35) yearspremenopausal and (45-60) years menopause was done, then the thickness ofmandibular inferior cortex and (DMFT) was evaluated. The results showed thatpanoramic radiographic measurements are considered as indicator of bone turnoverand the dentist is able to identify smokers and non-smokers postmenopausal femaleswith increase risk of osteopenia and osteoporosis by using dental panoramicradiography which is a simple valuable screening tool.